Fat Liberation Manifesto: November 1973 - Freespirit, Judy; Aldebaran, (Canadian Woman Studies/les cahiers de la femme, 2023)
The Fat Liberation Manifesto, originally written in 1973, by Judy Freespirit and Aldebaran.